A polymeric inclusion membrane and methods of making and using the same

CN116676494BActive Publication Date: 2026-10-27INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310660556.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-06
Publication Date
2026-10-27
Estimated Expiration
2043-06-06

AI Technical Summary

Technical Problem

CN114657374A公开了一种聚合物包容膜及其在金属离子提取方面的应用,聚合物包容膜萃取过程中,萃取剂甲基异丁酮或磷酸三丁酯合物和料液分别在两侧流动,将聚合物包容膜分离技术和溶剂萃取技术的结合应用于低品位复杂矿物浸出液中铜、镍、钻、锌等有色金属的萃取分离,但该发明提供的聚合物包容膜不能实现对低浓度锂资源的分离

Benefits of technology

[0044](1)本发明通过采用四苯硼钠和磷酸三丁酯做协同萃取剂,制得聚合物包容膜,所述聚合物包容膜对锂具有高选择性,能同时进行萃取和反萃取,能够高效绿色的从低浓度锂资源中分离出锂元素,使用操作方便简单、对环境友好。所述聚合物包容膜萃取剂用量少,在使用过程中萃取剂几乎不会流失,循环性、稳定性好,提升了所述聚合物包容膜的使用寿命,节约了使用成本,实现可连续且具有高选择性的锂分离,能够满足大批量工业化生产和应用

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004268764940000111
    Figure BDA0004268764940000111
  • Figure BDA0004268764940000116
    Figure BDA0004268764940000116
  • Figure BDA0004268764940000121
    Figure BDA0004268764940000121
Patent Text Reader

Abstract

The application provides a polymer inclusion membrane, a preparation method and application thereof. The polymer inclusion membrane comprises an extractant and a base polymer; the extractant comprises sodium tetraphenylborate and tributyl phosphate. The polymer inclusion membrane prepared by using sodium tetraphenylborate and tributyl phosphate as the synergistic extractant can realize high selectivity and strong stability of separation and enrichment of low-concentration lithium resources.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of membrane separation technology, specifically relating to a polymer-encapsulated membrane, its preparation method, and its application. Background Technology

[0002] Lithium resources are mainly distributed in lithium ore and salt lake brine. Lithium extraction methods from lithium ore primarily include acid leaching, sintering, and roasting, which offer advantages such as high lithium recovery rates, short production cycles, low costs, and simple processes. However, these methods are energy-intensive and cause severe environmental pollution. Lithium extraction from salt lake brine mainly involves precipitation, adsorption, and solvent extraction. However, precipitation is not suitable for treating brine with low lithium concentrations but high calcium and magnesium content; adsorption requires strict process control and has high adsorbent costs; solvent extraction suffers from high energy consumption and severe environmental pollution. Furthermore, during the evaporation process of preparing old brine, up to 50% of the lithium is lost due to entrainment by precipitated sodium chloride, carnallite, etc., resulting in significant resource waste. On the other hand, low-concentration lithium solutions, such as lithium ore tailings, raw salt lake brine, and lithium battery recycling wastewater, are difficult to recover and utilize due to their low lithium concentration and diverse impurities. To address these issues, membrane technology has been studied for its application in the extraction of low-concentration lithium resources.

[0003] CN115105973A discloses a method for preparing and applying a nanofiltration membrane for high-efficiency magnesium-lithium separation. The method involves mixing branched polyethyleneimine (molecular weight approximately 70,000) and piperazine hexahydrate into water to obtain an aqueous solution, and dissolving trimesoyl chloride in n-hexane to obtain an oil solution. The aqueous and oil solutions are first reacted on an ultrafiltration membrane substrate to form a dense polyamide layer on the membrane surface using interfacial polymerization. Then, the formed polyamide membrane is modified with an amino ionic liquid solution to obtain an amino ionic liquid-modified branched polyethyleneimine nanofiltration membrane (NH-2-IL / PEI / PA). The NH-2-IL / PEI / PA nanofiltration membrane obtained using this technique can achieve higher magnesium-lithium separation efficiency, but it suffers from problems such as easy pore clogging and short service life.

[0004] CN114713046A discloses an encapsulated ionic liquid support membrane for lithium extraction from salt lakes. The process involves coating a Nafion solution onto the upper surface of a porous substrate membrane, heating and drying to form an encapsulation layer, then applying adhesive to the sides of the porous substrate membrane and allowing it to cure at room temperature. Next, an ionic liquid is filled into the porous substrate membrane. Finally, a Nafion solution is coated onto the lower surface of the porous substrate membrane, heated and dried to form another encapsulation layer, resulting in the encapsulated ionic liquid support membrane. This technology yields an encapsulated ionic liquid support membrane that exhibits excellent Li-carboxylic acid (LCA) performance in lithium extraction from salt lakes. + It has good recovery performance, but there are problems such as easy clogging of the channels and easy loss of extractant.

[0005] Polymer-encapsulated membranes (PIMs) are a novel extraction liquid membrane technology, developed from support liquid membranes. They primarily consist of three components: a base polymer, an extractant, and a plasticizer, and are less prone to pore blockage. CN114657374A discloses a polymer-encapsulated membrane and its application in metal ion extraction. During the polymer-encapsulated membrane extraction process, the extractant, methyl isobutyl ketone or tributyl phosphate, and the feed solution flow on opposite sides. This combines polymer-encapsulated membrane separation technology with solvent extraction technology for the extraction and separation of non-ferrous metals such as copper, nickel, cobalt, and zinc in low-grade complex mineral leachates. However, the polymer-encapsulated membrane provided by this invention cannot achieve the separation of low-concentration lithium resources.

[0006] Therefore, there is a need to develop a polymer-encapsulated membrane that can achieve highly selective separation and enrichment of low-concentration lithium resources. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a polymer-encapsulated membrane, its preparation method, and its applications. The polymer-encapsulated membrane enables highly selective and stable separation and enrichment of low-concentration lithium resources.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a polymer-encapsulated membrane, the polymer-encapsulated membrane comprising an extractant and a base polymer;

[0010] The extractant includes sodium tetraphenylborate (NaBPh4) and tributyl phosphate (TBP).

[0011] The polymer-encapsulated membrane described in this invention uses sodium tetraphenylborate and tributyl phosphate as synergistic extractants, which have high selectivity for lithium and can achieve separation and enrichment of low-concentration lithium resources. In addition, the extractant contained in the polymer-encapsulated membrane is almost not lost during use, which improves the service life of the polymer-encapsulated membrane and has good stability.

[0012] In this invention, the low concentration refers to a concentration of 60-600ppm, such as 60ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, or 600ppm.

[0013] Preferably, the mass percentage of sodium tetraphenylborate in the polymer-encapsulated membrane is 6%-15%, such as 6%, 7%, 9%, 10%, 12%, 13%, or 15%.

[0014] In this invention, when the mass percentage of sodium tetraphenylborate in the polymer-encapsulated membrane is too high, the prepared polymer-encapsulated membrane is uneven and has undissolved sodium tetraphenylborate on its surface; when the mass percentage of sodium tetraphenylborate decreases, the separation effect of the polymer-encapsulated membrane decreases until it no longer has a separation effect.

[0015] Preferably, the base polymer comprises cellulose triacetate (CTA).

[0016] In this invention, the triacetic acid cellulose exhibits excellent stability and a certain degree of solubility in solvents, as well as excellent chemical resistance and hydrophobicity.

[0017] Preferably, the mass percentage of tributyl phosphate in the polymer-encapsulated membrane is 20-60%, such as 20%, 25%, 30%, 32%, 35%, 38%, 40%, 45%, 50%, 52%, 54%, 58%, or 60%.

[0018] Preferably, the mass percentage of the base polymer in the polymer-encapsulated membrane is 30-70%, such as 30%, 32%, 34%, 35%, 38%, 40%, 45%, 50%, 52%, 55%, 60%, 65%, or 70%.

[0019] In this invention, as the mass percentage of tributyl phosphate increases and the mass percentage of cellulose triacetate decreases in the polymer-encapsulated membrane, the separation effect of the polymer-encapsulated membrane shows a trend of first increasing and then decreasing. This is because if the content of tributyl phosphate is too low and the content of cellulose triacetate is too high, it will lead to unevenness of the polymer-encapsulated membrane, limiting the diffusion behavior of the extractant within the membrane and significantly reducing the transport flux. If the content of tributyl phosphate is too high and the content of cellulose triacetate is too low, the polymer-encapsulated membrane will be too soft, leading to a large loss of extractant, which in turn affects the stability and selectivity of the polymer-encapsulated membrane. At the same time, sodium tetraphenylborate and tributyl phosphate are a synergistic extraction system, and using a specific content ratio of tributyl phosphate results in better separation.

[0020] In a second aspect, the present invention provides a method for preparing a polymer-encapsulated membrane as described in the first aspect, the method comprising the following steps: mixing an extractant and a base polymer to obtain a polymer-encapsulated membrane.

[0021] Preferably, the mixing includes the following steps:

[0022] (1) Mix the extractant and organic solvent and stir to obtain a mixed solution.

[0023] (2) Mix the base polymer with the mixed solution obtained in step (1) and stir to obtain a homogeneous solution.

[0024] Preferably, the mixing process in step (2) further includes: ultrasonically treating the homogeneous solution obtained in step (2), spreading it into a solution layer, and drying it.

[0025] Preferably, the organic solvent includes dichloromethane.

[0026] Preferably, the mixing temperatures in steps (1) and (2) are each independently 25-40°C, such as 25°C, 28°C, 30°C, 32°C, 35°C, 36°C, 37°C, 38°C, 39°C, or 40°C.

[0027] Preferably, the stirring speeds in steps (1) and (2) are each independently 300-500 rpm, such as 300 rpm, 320 rpm, 350 rpm, 380 rpm, 400 rpm, 420 rpm, 450 rpm, 480 rpm, or 500 rpm.

[0028] Preferably, the stirring temperature in step (1) is 20-30℃ (e.g., 20℃, 22℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃ or 30℃, etc.), and the stirring time is 10-20min (e.g., 10min, 11min, 12min, 13min, 14min, 15min, 16min, 17min, 18min, 19min or 20min, etc.).

[0029] Preferably, the stirring temperature in step (2) is 20-30℃ (e.g., 20℃, 22℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃ or 30℃, etc.), and the stirring time is 5-10h (e.g., 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 9h or 10h, etc.).

[0030] Preferably, the drying temperature is 20-30℃ (e.g., 20℃, 22℃, 24℃, 25℃, 26℃, 27℃, 28℃, 29℃ or 30℃, etc.), and the drying time is ≥48h (e.g., 50h, 55h, 60h, 65h, 70h, 75h, 80h, 90h, 95h or 100h, etc.).

[0031] Thirdly, the present invention provides the application of the polymer-encapsulated membrane as described in the first aspect in materials for separating lithium from low-concentration lithium resources.

[0032] Preferably, the application includes the following steps: placing a feed liquid and a back-extraction liquid on both sides of the polymer-encapsulated membrane, so that the liquid levels of the feed liquid and the back-extraction liquid are on the same horizontal plane, and simultaneously stirring the feed liquid and the back-extraction liquid at the same speed.

[0033] In this invention, a feed solution containing a low concentration of lithium is placed on one side of the polymer-encapsulated membrane, and a back-extraction phase is placed on the other side. The feed solution, polymer-encapsulated membrane, and back-extraction solution form a sandwich structure system. The lithium ions (Li...) in the feed solution... + Interfacial extraction occurs at the interface between the polymer-encapsulated membrane and the feed solution, forming a lithium extractant. Subsequently, the lithium extractant diffuses via its concentration gradient, passes through the polymer-encapsulated membrane, and undergoes mass transfer to the interface between the polymer-encapsulated membrane and the back-extraction solution, where an interfacial back-extraction reaction occurs. + The lithium is introduced into the back-extraction solution for enrichment. Simultaneously, the extractant redisperses back to the interface between the polymer-encapsulated membrane and the feed solution using the concentration gradient, achieving efficient lithium extraction from low-concentration lithium resources. The reaction mechanism is as follows:

[0034] The phase interface between the polymer-encapsulated membrane and the feed solution: Li + When Li combines with the -P=O group on the TBP molecule, the metal ion provides an empty orbital, and the -P=O group provides a lone pair of electrons, thus forming a macromolecular complex. + Extraction from the aqueous phase to the organic phase, as shown in the following formula.

[0035] Li + +BPh4 - +sTBP=LiBPh4·sTBP

[0036] Wherein, s is 1, 2, 3 or 4.

[0037] The phase interface between the polymer-encapsulated membrane and the back-extraction solution: the generated lithium extract reacts with sodium carbonate at this interface, Na... + Replacing Li + Thus achieving Li + The desorption and extraction solvent recovery are shown in the following formula.

[0038] LiBPh4·sTBP+Na + =NaBPh4·sTBP+Li +

[0039] Wherein, s is 1, 2, 3 or 4.

[0040] Preferably, the feed solution comprises a Li-containing solution with a concentration of 60-600 ppm. + Solutions, such as 60ppm, 100ppm, 150ppm, 200ppm, 250ppm, 300ppm, 350ppm, 400ppm, 450ppm, 500ppm, or 600ppm.

[0041] Preferably, the back-extraction solution comprises a sodium carbonate solution with a concentration of 0.1-2.5 mol / L (e.g., 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L, or 2.5 mol / L).

[0042] Preferably, the stirring rate is 200-500 rpm, such as 200 rpm, 250 rpm, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 480 rpm, or 500 rpm.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] (1) This invention utilizes sodium tetraphenylborate and tributyl phosphate as synergistic extractants to prepare a polymer-encapsulated membrane. This polymer-encapsulated membrane exhibits high selectivity for lithium, enabling simultaneous extraction and back-extraction. It efficiently and environmentally friendly separates lithium from low-concentration lithium resources. The membrane is easy to use and simple to operate, and is environmentally friendly. The polymer-encapsulated membrane requires a small amount of extractant, resulting in minimal loss during use. It exhibits good recyclability and stability, extending the membrane's lifespan and saving on operating costs. This allows for continuous and highly selective lithium separation, meeting the needs of large-scale industrial production and applications.

[0045] (2) The polymer-enclosed membrane is used in low-concentration Li + Li in solution + In the separation of Li + The transmission throughput is 17.561 × 10⁻⁶. -3 -62.739×10 -3 mol m -2 h -1 In the preferred case, Li + The transmission throughput is 45.300 × 10 -3 -62.739×10 -3 mol m -2 h -1 ; Li in solutions with a high magnesium-to-lithium ratio (magnesium-to-lithium ratio ≤ 40) + Separation is performed, Li + The transmission throughput is 2.783 × 10⁻⁶. -3 -15.978×10 -3 mol m -2 h -1 The lithium-magnesium selectivity is 1.3543-10.2329. In the preferred case, Li... + The transmission throughput is 14.252 × 10⁻⁶. -3 -15.978×10-3 mol m -2 h -1 The lithium-magnesium selectivity ranged from 2.8346 to 10.2329; it could also achieve lithium-magnesium selectivity in high magnesium-to-lithium ratio solutions (magnesium-to-lithium ratio > 40). + Separate them. Detailed Implementation

[0046] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention.

[0047] Example 1

[0048] This embodiment provides a polymer-encapsulated membrane and its preparation method. The polymer-encapsulated membrane comprises 60% cellulose triacetate, 30% tributyl phosphate, and 10% sodium tetraphenylborate by mass percentage.

[0049] The preparation method includes the following steps:

[0050] (1) Mix 0.1250g of sodium tetraphenylborate, 0.3750g of tributyl phosphate and 25mL of dichloromethane, and stir for 15min at 400rpm and 25℃.

[0051] (2) Mix 0.7500g of cellulose triacetate with the mixed solution obtained in step (1), stir for 5h at 500rpm and 25℃, and sonicate to obtain a homogeneous mixed solution. Then spread the homogeneous solution into a solution layer and dry it at 25℃ for 60h to obtain the polymer-encapsulated membrane.

[0052] Example 2

[0053] This embodiment provides a polymer-encapsulated membrane and its preparation method. The polymer-encapsulated membrane comprises 30% cellulose triacetate, 60% tributyl phosphate, and 10% sodium tetraphenylborate by mass percentage.

[0054] The preparation method includes the following steps:

[0055] (1) Mix 0.1250g of sodium tetraphenylborate, 0.7500g of tributyl phosphate and 25mL of dichloromethane, and stir for 10min at 300rpm and 30℃.

[0056] (2) Mix 0.3750g of cellulose triacetate with the mixed solution obtained in step (1), stir for 10h at 500rpm and 20℃, and sonicate to obtain a homogeneous mixed solution. Then spread the homogeneous solution into a solution layer and dry it at 20℃ for 65h to obtain the polymer-encapsulated membrane.

[0057] Example 3

[0058] This embodiment provides a polymer-encapsulated membrane and its preparation method. The polymer-encapsulated membrane comprises, by mass percentage, 50% cellulose triacetate, 40% tributyl phosphate, and 10% sodium tetraphenylborate.

[0059] The preparation method includes the following steps:

[0060] (1) Mix 0.1250g of sodium tetraphenylborate, 0.5000g of tributyl phosphate and 25mL of dichloromethane, and stir for 20min at 400rpm and 25℃.

[0061] (2) Mix 0.6250g of cellulose triacetate with the mixed solution obtained in step (1), stir for 8 hours at 400 rpm and 25°C, and sonicate to obtain a homogeneous mixed solution. Then spread the homogeneous solution into a solution layer and dry it at 25°C for 50 hours to obtain the polymer-encapsulated membrane.

[0062] Example 4

[0063] This embodiment provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and that in Example 1 is that the tributyl phosphate is 35%, the sodium tetraphenylborate is 5%, the sodium tetraphenylborate in step (1) is 0.0625g, and the tributyl phosphate is 0.4375g. The other raw materials, dosages and preparation methods are the same as in Example 1.

[0064] Example 5

[0065] This embodiment provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and that in Example 1 is that the tributyl phosphate is 20%, the sodium tetraphenylborate is 20%, the sodium tetraphenylborate in step (1) is 0.2500g, and the tributyl phosphate is 0.2500g. Other raw materials, dosages, and preparation methods are the same as in Example 1.

[0066] Example 6

[0067] This embodiment provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and that in Example 1 is that the polymer-encapsulated membrane comprises 20% cellulose triacetate and 70% tributyl phosphate by mass percentage. In step (1), the amount of tributyl phosphate is 0.8750g, and in step (2), the amount of cellulose triacetate is 0.2500g. Other raw materials, amounts, and preparation methods are the same as in Example 1.

[0068] Example 7

[0069] This embodiment provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and that in Example 1 is that the polymer-encapsulated membrane comprises 80% cellulose triacetate and 10% tributyl phosphate by mass percentage. In step (1), the amount of tributyl phosphate is 0.1250g, and in step (2), the amount of cellulose triacetate is 1.0000g. Other raw materials, amounts, and preparation methods are the same as in Example 1.

[0070] Example 8

[0071] This embodiment provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and that in Example 1 is that the tributyl phosphate is 34%, the sodium tetraphenylborate is 6%, the sodium tetraphenylborate in step (1) is 0.0750g, and the tributyl phosphate is 0.4250g. The other raw materials, dosages and preparation methods are the same as in Example 1.

[0072] Example 9

[0073] This embodiment provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and that in Example 1 is that the tributyl phosphate is 25%, the sodium tetraphenylborate is 15%, the sodium tetraphenylborate in step (1) is 0.1875g, and the tributyl phosphate is 0.3125g. The other raw materials, dosages and preparation methods are the same as in Example 1.

[0074] Comparative Example 1

[0075] This comparative example provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and Example 1 is that the extractant is only tributyl phosphate, and the mass of tributyl phosphate in step (1) is 0.5000g. Other raw materials, dosages and preparation methods are the same as in Example 1.

[0076] Comparative Example 2

[0077] This comparative example provides a polymer-encapsulated membrane and its preparation method. The only difference between the polymer-encapsulated membrane and Example 1 is that the extractant is sodium tetraphenylborate, and the mass of sodium tetraphenylborate in step (1) is 0.5000g. Other raw materials, dosages and preparation methods are the same as in Example 1.

[0078] The polymer-encapsulated films provided in the examples and comparative examples were subjected to the following performance tests.

[0079] (1) Low concentration of Li + Separation:

[0080] The polymer-encapsulated films provided in the examples and comparative examples were cut to obtain an effective area of ​​10.2 cm². 2 The polymer-encapsulated membrane was fixed and 100 mL of Li containing 60 mg / L was added.+ The feed solution and 100 mL of 0.2 mol / L sodium carbonate solution were placed on the two layers of the polymer-encapsulated membrane, forming the elution phase. The liquid levels of the feed solution and sodium carbonate solution were kept equal. Magnetic stirring in both phases was turned on and maintained at 400 rpm, allowing Li to be stirred simultaneously on both sides of the polymer-encapsulated membrane. + Extraction and back-extraction were performed. After 24 hours of continuous extraction, the Li content in the feed solution and sodium carbonate solution was measured. + The concentration of Li + Transmission throughput.

[0081] (2) For Li in solutions with a high magnesium-to-lithium ratio + Selective separation

[0082] The polymer-encapsulated films provided in the examples and comparative examples were cut to obtain an effective area of ​​10.2 cm². 2 Fix the polymer-encapsulated membrane and then place 100 mL of Li-containing... + 60 mg / L and Mg 2+ A 2400 mg / L feed solution and 100 mL of 0.2 mol / L sodium carbonate solution were placed on either side of the polymer-encapsulated membrane to form the elution phases. The liquid levels of the feed solution and sodium carbonate solution were kept equal. Magnetic stirring was turned on in both phases and maintained at 400 rpm to allow LiO2 to be stirred simultaneously on both sides of the polymer-encapsulated membrane. + Extraction and back-extraction were performed. After 24 hours of continuous extraction, Li was determined. + Transport throughput and lithium-magnesium selectivity.

[0083] Lithium-magnesium selectivity:

[0084]

[0085] in and Li, representing sodium carbonate solution, respectively + and Mg 2+ concentration, and These represent the initial Li values ​​of the feed solution. + and Mg 2+ concentration.

[0086] (3) For Li in high magnesium-to-lithium ratio solutions + Selective separation

[0087] The polymer-encapsulated films provided in Examples 1 and 3 were cut to obtain an effective area of ​​10.2 cm². 2 Fix the polymer-encapsulated membrane and then place 100 mL of Li-containing... + 60 mg / L and Mg 2+A 72000 mg / L feed solution and 100 mL of 0.2 mol / L sodium carbonate solution were placed on either side of the polymer-encapsulated membrane to form the elution phases. The liquid levels of the feed solution and the sodium carbonate solution were kept equal. Magnetic stirring was turned on in both phases and maintained at 400 rpm to allow LiO2 to be stirred simultaneously on both sides of the polymer-encapsulated membrane. + Extraction and back-extraction were performed. After 8 hours of continuous extraction, Li was determined. + Transport throughput and lithium-magnesium selectivity.

[0088] Lithium-magnesium selectivity:

[0089]

[0090] in and Li, representing sodium carbonate solution, respectively + and Mg 2+ concentration, and These represent the initial Li values ​​of the feed solution. + and Mg 2+ concentration.

[0091] The test results are shown in Table 1.

[0092] Table 1

[0093]

[0094] In Table 1, "-" indicates that the result was not measured.

[0095] According to the test results in Table 1, the polymer-encapsulated membranes provided in Examples 1-9 can withstand low concentrations of Li. + Li in solution + In the separation of Li + The transmission throughput is 17.561 × 10⁻⁶. -3 -62.739×10 -3 mol m -2 h -1 It can achieve the effect of low concentration Li + Separation was performed on Li in a solution with a high magnesium-to-lithium ratio. + Separation is performed, Li + The transmission throughput is 2.783 × 10⁻⁶. -3 -15.978×10 - 3 mol m -2 h -1 The lithium-magnesium selectivity was 1.3543-10.2329. The polymer-encapsulated films provided in Examples 1-3 exhibited good lithium-magnesium selectivity at low concentrations of Li. + Li in solution + In the separation of Li+ The transmission throughput is 45.300 × 10 -3 -62.739×10 -3 mol m -2 h -1 ; Li in solutions with a high magnesium-to-lithium ratio + Separation is performed, Li + The transmission throughput is 14.252 × 10⁻⁶. -3 -15.978×10 -3 mol m -2 h -1 The lithium-magnesium selectivity was 2.8346-10.2329; the polymer-encapsulated films provided in Examples 1 and 3 exhibited good lithium-magnesium selectivity in high magnesium-to-lithium ratio solutions. + Separation is performed, Li + The transmission throughput is 3.1516 × 10⁻⁶. -3 -6.3545×10 -3 mol m -2 h -1 The lithium-magnesium selectivity was 282.5-384.9, with a specificity for Li. + It has high selectivity.

[0096] Compared with Example 1, Example 4 shows that the mass percentage of sodium tetraphenylborate is too low, therefore Li + The transport flux decreased, the lithium-magnesium selectivity decreased, and the separation effect of the polymer-encapsulated membrane decreased. Compared with Example 1, Example 5 shows that if the mass percentage of sodium tetraphenylborate is too high, the prepared polymer-encapsulated membrane is extremely uneven, and sodium tetraphenylborate solids can be observed on the membrane surface, indicating poor stability. Li + The decrease in transport flux, lithium-magnesium selectivity, and separation efficiency demonstrates that the polymer-encapsulated membrane prepared using sodium tetraphenylborate and tributyl phosphate with specific amounts of extractant has better performance.

[0097] Compared with Example 1, Example 6 shows that if the mass percentage of tributyl phosphate is too high, the resulting polymer-encapsulated film will be too soft. + A large amount of extractant is lost during the transport process, Li + The transmission flux, lithium-magnesium selectivity, and stability all decreased; compared with Example 1, Example 7 shows that if the mass percentage of tributyl phosphate is too low, the prepared polymer-encapsulated film will be too hard, and Li + The decreased transport flux, lithium-magnesium selectivity, and stability, along with the reduced separation efficiency, demonstrate that the polymer-encapsulated membrane prepared using a specific ratio of cellulose triacetate and extractant exhibits superior performance.

[0098] Compared with Example 1, Example 8 shows that the mass percentage of sodium tetraphenylborate is smaller, thus the Li in the prepared polymer-encapsulated film is lower. +The transmission flux and lithium-magnesium selectivity decreased slightly; compared with Example 1, Example 9 shows that the mass percentage of sodium tetraphenylborate is larger, thus the Li in the prepared polymer-encapsulated film is... + The slight decrease in transport throughput and lithium-magnesium selectivity demonstrates that the polymer-encapsulated membrane prepared with 10% sodium tetraphenylborate by mass has better performance.

[0099] Compared to Example 1, if the extractant is only tributyl phosphate (Comparative Example 1), the resulting polymer-encapsulated membrane cannot produce a separation effect. Compared to Example 1, if the extractant is only sodium tetraphenylborate (Comparative Example 2), the prepared polymer-encapsulated membrane is extremely non-uniform, and sodium tetraphenylborate solids can be observed on the membrane surface. After a period of transport, the membrane leaks and ruptures, failing to produce a separation effect. This demonstrates that only the synergistic use of tributyl phosphate and sodium tetraphenylborate can produce Li. + The effect of separation.

[0100] The applicant declares that the present invention is illustrated by the above embodiments to demonstrate a polymer-encapsulated membrane, its preparation method, and its application. However, the present invention is not limited to the above embodiments, i.e., it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials of the product of the present invention, addition of auxiliary components, and selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. The application of a polymer-encapsulated membrane in materials for separating lithium from low-concentration lithium resources, characterized in that, The polymer-encapsulated membrane comprises an extractant and a base polymer; The extractant includes sodium tetraphenylborate and tributyl phosphate; The base polymer includes cellulose triacetate; The mass percentage of sodium tetraphenylborate in the polymer-encapsulated membrane is 6%-15%; The mass percentage of tributyl phosphate in the polymer-encapsulated membrane is 20-60%. The application includes the following steps: placing a feed solution and a back-extraction solution on both sides of the polymer-encapsulated membrane, so that the liquid levels of the feed solution and the back-extraction solution are at the same horizontal level, and simultaneously stirring the feed solution and the back-extraction solution at the same speed; the back-extraction solution includes a sodium carbonate solution with a concentration of 0.1-2.5 mol / L.

2. The application according to claim 1, characterized in that, The polymer-encapsulated membrane contains 30-70% by mass of the base polymer.

3. The application according to claim 1 or 2, characterized in that, The method for preparing the polymer-encapsulated membrane includes the following steps: mixing an extractant and a base polymer to obtain a polymer-encapsulated membrane.

4. The application according to claim 3, characterized in that, The mixing process includes the following steps: (1) Mix the extractant and the organic solvent, stir, and obtain a mixed solution; (2) Mix the base polymer with the mixed solution obtained in step (1) and stir to obtain a homogeneous solution.

5. The application according to claim 4, characterized in that, Step (2) further includes: ultrasonically treating the homogeneous solution obtained in step (2), spreading it into a solution layer, and drying it.

6. The application according to claim 4, characterized in that, The organic solvent includes dichloromethane.

7. The application according to claim 4, characterized in that, The mixing temperatures in steps (1) and (2) are each independently 25-40°C.

8. The application according to claim 4, characterized in that, The stirring rates in steps (1) and (2) are each 300-500 rpm.

9. The application according to claim 4, characterized in that, The stirring temperature in step (1) is 20-30℃, and the stirring time is 10-20 min.

10. The application according to claim 4, characterized in that, The stirring temperature in step (2) is 20-30℃, and the stirring time is 5-10 h.

11. The application according to claim 5, characterized in that, The drying temperature is 20-30℃, and the drying time is ≥48 h.

12. The application according to claim 1, characterized in that, The feed solution includes a Li-containing solution with a concentration of 60-600 ppm. + Solution.

13. The application according to claim 1, characterized in that, The stirring speed is 200-500 rpm.

Citation Information

Patent Citations

  • Polymer containing membrane and application thereof in metal ion extraction

    CN114657374A

  • Preparation method and application of nanofiltration membrane for efficient magnesium-lithium separation

    CN115105973A